Preventive effect of cranberries with high dose of proanthocyanidins on urinary tract infections: a meta-analysis and systematic review - Xiong, Zheyu; Gao, Yongli; Yuan, Chi; Jian, Zhongyu; Wei, Xin (Frontiers in Nutrition, 2024)
One of the most prevalent bacterial diseases in both the general population and hospitals are urinary tract infections (UTIs). There is still conflicting scientific data about the usefulness of cranberry products in preventing UTIs. Our meta-analysis investigated whether the content of the main component, proanthocyanidins (PACs), in cranberries affects their ability to prevent UTIs. The average daily intake of PACs has already been reported in previous randomized controlled trials (RCTs) that intended to investigate the effectiveness of cranberry in preventing UTIs, which were collected in our meta-analysis. The results were reported as the number of participants with UTIs.Random effect or fixed effect models were chosen for statistical analysis based on the heterogeneity.Ten RCTs that matched the requirements were included. The results showed that when the daily intake of PACs was at least 36mg, the risk of UTIs was reduced by 18% (RR=0.82, 95%CI=0.69-0.98, P=0.03). But when the daily intake of PACs was less than 36 mg, there was no statistical significance risk decrease (P=0.39). The results of the sub-group analysis showed that cranberries only significantly reduced the risk of UTIs when the duration of cranberry product use falls between 12 and 24 weeks (RR=0.75, 95%CI=0.61-0.91, P=0.004). Additionally, cranberries also significantly reduced the risk of UTIs only in subgroups that just included females (RR=0.84, 95%CI=0.71-0.98, P=0.02). These findings showed a strong correlation between the daily use of the active ingredient PACs found in cranberry products and the prevention of UTIs. Our meta-analysis is the first to show that there are minimum daily PAC consumption intake levels in cranberry products and length of use considerations that are needed to achieve clinically relevant UTI prevention benefits.